Peran Kelompok Masyarakat Pengelola Wisata Mangrove Trail Tiwoho Taman Nasional Bunaken - Anggreyni Runtunuwu; Fabiola B. Saroinsong; Wawan Nurmawan (AGRI-SOSIOEKONOMI, 2022)
This study aims to determine the role of community groups managing the Tiwoho Mangrove Trail tourism in Tiwoho Village, Wori District, North Minahasa Regency. The study was conducted in March 2022. The method used in this study is the purposive sampling method. The sample taken was 35 respondents, the data source used primary and secondary data and was analyzed descriptively through the presentation of descriptions, images, and tables. The results of the study indicate the role of the management group in the planning stage, namely planning a work program for the construction of the Tiwoho Mangrove Trail, then in the implementation stage, namely building Mangrove Trail Tiwoho tourism and holding mangrove conservation activities and complementing the supporting facilities in tourist attractions, then in the utilization stage the group utilizes the community, government and related agencies to support the needs of the Tiwoho Mangrove Trail tour. There is no Original Village Income (VOI) yet but the Tiwoho Mangrove Trail tour has a good impact on the village and the surrounding community. All members of the group play an active role in the management of the Tiwoho Mangrove Trail tour. The role of the community group managing the Mangrove Trail Tiwoho tourism starting from planning, implementing and utilizing is well carried out.